Analysis of E-Learning Management Development at High School Level - Didik Himmawan; Nesa Fitriyani Hasanah; Dhiah Farah Dhifa; Fitri Nurul Hidayah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
E-learning is a learning process that systematically uses information and communication technology and combines various learning elements, such as time and space interactions. In its development stage, e-learning is not only for presenting online teaching materials but must be more creative, communicative, and innovative. This study aims to find out about the development of e-learning in high schools. This descriptive research method uses a quantitative method. This study was conducted by distributing questionnaires online to high school students via Google Forms. The data analysis method for this study used Microsoft Excel and Spss version 25 to test normality, completeness, and improvement in learning outcomes. The research subjects were 36 high school students. The development of network utilization in schools has supported the use of web-based e-learning systems using synchronous and asynchronous systems, both individually and simultaneously in ongoing learning activities. E-learning can provide convenience in interaction between teachers and students to achieve understanding of the teaching materials or materials taught.